Online User Behaviour in Delhi - A Factor Analysis - Sajeevan Rao, A.; Mehdi, Mokhalles Mohd (Indian Journal of Marketing, 2010)
The world is moving towards Electronic Commerce activities at a very fast pace. Internet enables consumers to perform many stages of the sales process in a quick and efficient manner. It also provides comprehensive product information, facilitates comparison shopping, and allows for a condensed sales process. Online buying refers to buying through the Internet. Online buying assists buyers’ anywhere, offering a platform with immense flexibility. Internet buying provides an opportunity to individuals to buy and sell products using a company’s website. According to the Internet in India [I Cube] 2007 report published jointly by the Internet and Mobile Association of India and IMRB International, the number of internet users in India in the ever user or claimed user category touched 46 million in September 2007 from 32.2 million in September 2006. During the same period, the number of active internet users reached 32 million from 21.1 million (Source: IMRB).